PERAN WANITA KARIR DALAM MEMBENTUK KARAKTER ANAK DI IAIN KERINCI - Titin titin Kusayang (LPPM Universitas Muhammadiyah Muara Bungo, 2022)
This research is qualitative research. It has the purpose to explain the roles of career mothers in forming her children characters and the children’s character of career mother in State Islamic Institute of Kerinci. The informants were selected through purposive sampling. Then, the informants were interviewed to collect the data. The data were analyzed through data reduction, data display, and conclusion. The research findings showed that the roles of career mother in forming the characters of children were educating children by modeling, applying early education system for children, doing habituations and giving advice for children. Then, the children’s characters of career mothers are honest, responsible and independent.